Case‐Control Study on a Decade of Ground‐Based Magnetometers in California Reveals Modest Signal 24–72 hr Prior to Earthquakes. Issue 10 (29th September 2022) - Heavlin, William D.; Kappler, Karl; Yang, Lusann; Fan, Minjie; Hickey, Jason; Lemon, James; MacLean, Laura; Bleier, Thomas; Riley, Patrick; Schneider, Daniel
Abstract: Magnetic field changes as earthquake precursors have been the subject of numerous studies and some controversy. Infrequent large earthquakes and sparse magnetometer coverage along fault zones complicate statistical analysis. We present an analysis of ground‐based magnetic time‐series measurements before 19 earthquakes ≥M4.5 in California drawing from over 330, 000 site‐days of measurement spanning a decade. To perform a fair existential test for electromagnetic antecedents we applied a pre‐specified statistical analysis with two key ideas. First, we combine signals from nearby (≤40 km) sites via spectral cross‐power, and then look for large spikes in frequency domain (0.016–25 Hz). The former is only possible with a dense set of sites running over a long period of time. In this statistical case‐control study we used the machine learning concept of rigorously separated train and test sets of earthquakes which were generated via a rule‐based query of the USGS earthquake catalog. Before each declustered earthquake, we constructed one period 24–72 hr before (the "precursor" or " p ‐period") and a series of seven equally‐sized preceding periods ("quiescent" or " q ‐periods"). We distilled the data in each period to a frequency‐dependent feature—the 98th percentile of spectral cross power. We trained a model based on Linear Discriminant Analysis and applied the discriminator to the test set revealing a modest effect in the days leading up to an earthquake. While the observed effect size is not directly useful for earthquake prediction (long a scientific goal), it suggests a relationship which should be further investigated for a physical link. Plain Language Summary: We identified changes in the magnetic field near intermediate‐large earthquakes in California in the days before the earthquakes happened. The statistical signal is of modest size, which means that we can not directly provide a prediction that can be used to alert the public. This study provides evidence that there is a physical change that can be observed in the days before an earthquake, but further scientific study is needed to understand this process. Key Points: Frequency domain analysis of ground‐based magnetometer data shows a modest change in days leading up to intermediate‐large ( M ≥ 4.5) earthquakes One novel part of the analysis is the use of cross‐power signals, which combines the signals from instruments separated by tens of km A supplementary analysis of the data with first order global geomagnetic effects subtracted increased the measured effect size significantly